Unique microRNA expression in the colonic mucosa during chronic HIV-1 infection. (10th September 2017) - Fulcher, Jennifer A.; Koukos, Georgios; Koutsioumpa, Marina; Elliott, Julie; Drakaki, Alexandra; Iliopoulos, Dimitrios; Anton, Peter A.
Abstract : Objective: Chronic HIV-1 infection leads to widespread inflammation and immune dysregulation. The gastrointestinal mucosa, a primary site for HIV-1 replication, is thought to play a significant role in this response. MicroRNAs (miRs) are small noncoding RNAs that regulate gene expression, including immune activation and inflammation. Here we investigate miR expression and function in the colonic mucosa during HIV-1 infection. Design and methods: Using miR profiling, we examined miR expression in the colonic mucosa of HIV-infected patients. These miRs were further parsed to identify those that most likely function in HIV-related inflammation. Using bioinformatics tools, we identified potential target genes which were confirmed using in-vitro functional testing. Results: We identified 12 miRs that were differentially expressed in the colonic mucosa of HIV-infected patients with high versus undetectable plasma viral concentrations. Of these, both miR-26a and miR-29a were downregulated in untreated HIV-1 infection, yet not in the colonic mucosa from inflammatory bowel disease. This downregulation occurs within the first hours after infection. These miRs were further shown to directly target IL-6 and STAT3, respectively, with similar changes confirmed in an ex-vivo explant infection model. Conclusion: miR-26a and miR-29a levels are decreased in the colonic mucosa during chronic HIV-1 infection, and this change may be initiated during acute infection. Both miRs de-repress the IL-6/STAT3 signaling pathway, which could contribute to increased inflammation during infection. These miRs may represent novel therapeutic targets for HIV-1-associated inflammation in the colonic mucosa. Abstract : Supplemental Digital Content is available in the text